PENGARUH VISUAL MERCHANDISING DAN STORE ATMOSPHERE TERHADAP IMPULSE BUYING PADA KONSUMEN OH!SOME DI DUTAMALL BANJARMASIN - Nur Asiyah; Nurul Wahyuni; Devi Rusvitawati; Humaidi (Smart Business Journal (SBJ), 2026)
ABSTRACT This research is undertaken to examine the partial as well as concurrent influences of visual merchandising and store atmosphere on impulse buying behavior among customers at OH!SOME Duta Mall Banjarmasin. A quantitative methodological design was implemented, encompassing 100 participants determined through an accidental sampling method. Data acquisition was conducted by means of a systematically arranged questionnaire and subsequently processed using multiple linear regression analysis with IBM SPSS Statistics version 25. The results reveal that both visual merchandising and store atmosphere independently demonstrate a statistically significant positive impact on impulse buying. Moreover, these two variables collectively exhibit a significant effect on impulse buying behavior among customers at OH!SOME Duta Mall Banjarmasin.